PENGARUH PEMBERIAN EKSTRAK ETANOLIK RIMPANG JAHE MERAH TERHADAP FAGOSITOSIS MAKROFAG PADA MENCIT JANTAN YANG DIINFEKSI DENGAN Listeria monocytogenes - YS Bintari; Sudarsono Sudarsono; Agustinus Yuswanto (Majalah Obat Tradisional, 2010)
Ginger is one of some medicinal plants that has been used to make someone still in the comfortable condition e.g. headache, diarrhea, flatulent, cold, cough, and masuk angin. The purpose of this study was to determine effects of pungent principle extract of the “jahe merah” rhizome in the relation of increasing macrophage phagocytic activation. This method was done by using latex beads.( Leijh et al., (1986) The effects of 10 mg/kgBW, 25 mg/kgBW, and 100 mg/kgBW of pungent principle extract of “jahe merah” rhizome ethanolic extract, that extracted by 70%v/v Ethanol  was decided according to the number of latex which was phagocyted  by macrophages. The conditioning time was done in 20 days. At 15th day, mice were infected by Listeria monocytogenes. The data was analyzed by Kolmogorov-Smirnov, and one way ANOVA with by 95% confidence level. As the specific parameter of the pungent principle extract were: pungent principle spot 1 : 2  = 6.8:1; 3.27%w/w GAE (Gallic Acid Equivalent) as total phenolic concentration, and IC50 14.57 mg/mL. The result was shown that 100 mg/kgBW of 70% ethanolic extract of “jahe merah” rhizome, was capable to increase macrophage activity. The effect of increasing macrophage phagocytosis of 100 mg/kgBW of 70% ethanolic extract of jahe merah was the same with Echinacea extract and Levamisol.